Computed cell cycle and DNA histogram analyses in image cytometry in breast cancer. Issue 9 (September 1993) - Montironi, R; Diamanti, L; Santinelli, A; Magi Galluzzi, C; Scarpelli, M; Giannulis, I; Mangili, F
Abstract : AIMS--To analyse the cell cycle and DNA histogram components in data from DNA static cytometry and, in particular, to investigate the influence of the length of time the slides are exposed to the light of the cytophotometer in evaluating the G0/G1 peak. METHODS--DNA static cytometry was performed on 18 Feulgen stained imprints and six histological sections taken from six breast carcinomas. The total optical density values obtained were analysed using software commercially available as Multicycle. DNA flow cytometry was performed on the same cases. RESULTS--The proportions of nuclei related to the cell cycle components from DNA static cytometric data, obtained from Feulgen stained cytological smears, were almost identical with those obtained from DNA flow cytometric data. Moreover, additional information was obtained from the DNA static cytometry frequency histogram and the proportions of nuclei below the diploid G0/G1 peak and above the G2 phase. Discrepancies between DNA static cytometry and DNA flow cytometry were seen in the large coefficients of variation of the G0/G1 peaks obtained with the former method of analysis, even though a better correspondence was found when the exposure time of the slides to the light of the cytophometer was conspicuously shortened. The information obtained from histological sections seemed to be similar to that obtained from DNA flow cytometry when a single cell population was present; a single cell population was detected in two out of the three cases in which two distinct populations had been present in DNA flow cytometry. CONCLUSIONS--The computer analysis of DNA static cytometric data obtained from Feulgen stained cytological specimens provides the type of information on the cell cycle which is usually obtainable only from DNA flow cytometry. Correspondence with the DNA data from histological sections, however, was poor.